True optical resolution beyond the Rayleigh limit achieved by standing wave illumination - Frohn, Jan T. (The National Academy of Sciences, 2000)
During the last decade, various efforts have been undertaken to enhance the resolution of optical microscopes, mostly because of their importance in biological sciences. Herein, we describe a method to increase the resolution of fluorescence microscopy by illuminating the specimen with a mesh-like interference pattern of a laser source and electronic postprocessing of the images. We achieve 100-nm optical resolution, an improvement by a factor of more than 2 compared with standard fluorescence microscopy and of 1.5 compared with confocal scanning.